DIGITAL LOGISTICS - Kayumova Parizoda (European Science Publishing, 2024)
The advent of digital technology has transformed the way businesses operate, and the logistics industry is no exception. The integration of digital tools and techniques has given rise to digital logistics, a paradigm shift that is revolutionizing the supply chain management landscape. Digital logistics refers to the use of digital technologies, such as IoT, artificial intelligence, blockchain, and analytics, to optimize and streamline the logistics process. This article will explore the concept of digital logistics, its benefits, and its implications for the logistics industry.
Keywords: digital logistics, globalization, international organizations, logistic companies, digital platforms.